2019
DOI: 10.1096/fj.201801584r
|View full text |Cite|
|
Sign up to set email alerts
|

Sertoli cell–specific coxsackievirus and adenovirus receptor regulates cell adhesion and gene transcriptionviaβ‐catenin inactivation and Cdc42 activation

Abstract: Blood‐testis barrier (BTB) and apical ectoplasmic specialization (ES) serve as structural supports for germ cell (GC) development. We demonstrated that the Sertoli cell (SC)‐specific coxsackievirus and adenovirus receptor (CXADR) knockout (SC‐CXADR−/−), but not the GC‐specific knockout, impaired spermatogenesis. An increase in GC apoptosis and premature loss of elongated spermatids were observed in SC‐CXADR−/− testes. The BTB function was compromised in SC‐CXADR−/− testes with dysregulation of oocludin and zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…It is thus possible that Amh-Cre (Jackson) is not transcriptionally active in a subset of Sertoli cells. Consistent with our findings on those Amh-Cre mouse models, Huang et al also observed the mosaic deletion within the Sertoli cell population when using Amh-Cre (Jackson) [43]. However, other studies used the same Amh-Cre (Jackson) strain, but did not find such an incomplete Cre recombinase activity [44][45][46].…”
Section: Discussionsupporting
confidence: 92%
“…It is thus possible that Amh-Cre (Jackson) is not transcriptionally active in a subset of Sertoli cells. Consistent with our findings on those Amh-Cre mouse models, Huang et al also observed the mosaic deletion within the Sertoli cell population when using Amh-Cre (Jackson) [43]. However, other studies used the same Amh-Cre (Jackson) strain, but did not find such an incomplete Cre recombinase activity [44][45][46].…”
Section: Discussionsupporting
confidence: 92%
“…It has been proposed that CDC42 (through its interactions with TGF- or other extracellular pathways) ultimately signals directly through JNK or indirectly through Ras/ERK and p38 to elicit cellular responses (Lui et al, 2003;Wong et al, 2005;Xia and Cheng, 2005). Recently, CDC42 was implicated in mediating mTORC1 signaling downstream of NC1 peptide-mediated BTB remodeling via actin and microtubule cytoskeletal reorganization (Su and Cheng, 2019), as well as being a downstream mediator of coxsackievirus and adenovirus receptor (CXADR) signaling to regulate BTB and apical ES integrity and function (Huang et al, 2019). In vitro studies using dominant-negative constructs demonstrated that Cdc42 is required for TGF--induced BTB breakdown (Wong et al, 2010), which normally occurs when preleptotene spermatocytes traverse the BTB, suggesting that this activity is mediated via the GTP-active form of CDC42.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the tamoxifen-inducible CXADR knockout models, two testicular cell type-specific CXADR mouse models named germ cell-specific and Sertoli cell (SC)-specific CXADR knockout have been generated [ 47 ]. Two loxP sites flanking exon 3 of the Cxadr gene are inserted to generate floxed mice.…”
Section: Cxadr Knockout and Overexpression Mouse Modelsmentioning
confidence: 99%
“…Two loxP sites flanking exon 3 of the Cxadr gene are inserted to generate floxed mice. Floxed mice were then crossed with stimulated by retinoic acid 8 (Stra8)-Cre and anti-Mullerian hormone (Amh)-Cre mouse strains, respectively, to generate germ cell-specific knockout (GC-CXADR, Cxadr flox/flox ; Stra8-iCre) and Sertoli cell-specific CXADR knockout (SC-CXADR, Cxadr flox/flox ; Amh-iCre) mice [ 47 ]. GC-CXADR mice display no apparent abnormality in testicular size and tubular morphology compared to age-matched controls [ 47 ].…”
Section: Cxadr Knockout and Overexpression Mouse Modelsmentioning
confidence: 99%